Temperature gradients in targets at low energy high-intensity ion implantation; Surface and Coatings Technology; Vol. 389 - Ryabchikov A. I. Aleksandr Ilyich; Ananin P. S. Petr Semenovich; Bleykher (Bleicher) G. A. Galina Alekseevna; Bumagina A. I. Anna Ivanovna; Koval T. V. Tamara Vasilievna; Modebadze G. S. Georgy Slavovich (2020, 2020)
Title screen